Effect of Financial Performance and Company Size on Share Value - Islamiyati, Dian; Faruqi, Faris (Santoso Academy Network, 2023)
The goal of this study is to see how financial performance and company size affect share value in real estate and property companies listed on the Indonesia Stock Exchange between 2015 and 2019. The population of this study consists of all Indonesian real estate and property companies. For data collection, the official website documentation of the Stock Exchange is used. The purposive sampling method was used to collect 19 company samples. According to the study's findings, the activity variable as a proxy for asset turnover and the firm size variable have a negative and significant effect on stock value, whereas the profitability variable as a proxy for return on equity and leverage as a proxy for debt to equity have a positive and significant effect.